Uso de recursos alimenticios centroamericanos para el fomento de la industria animal. II. Composición química de la semilla y de la harina de torta de ajonjolí (Sesamum indicum) - Zaghi, Silvia de.; BRESSANI, R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
The study includes the chemical composition, mineral, vitamin and essential amino acid composition of 7 varieties of sesame seed (Sesamum indicum) and of 8 samples of sesame meal. The results showed significant differences in oil content between varieties. Processing methods is an important factor in determining the chemical composition of sesame meal, since solvent extraction of the oil produces meals with less oil and greater concentration of protein in comparison with meals produced by screw press methods. Essential amino acid content between varieties was similar with the possible exception of tryptophan. One variety, ´Venezuela 52´, showed different values in lencine, isolencine, and histidine than the other varieties